Efficacy of empowerment strategies for patients with hypertension: A systematic review and meta-analysis. Issue 5 (May 2020) - Zhao, Jingying; Hu, Yanan; Zhang, Xi; Zhang, Guangqing; Lin, Meizhen; Chen, Xiaoyin; Lin, Xiaoli; Wang, Xia
Highlights: The empowerment strategies could decrease SBP. The empowerment strategies could decrease DBP. The impacts of the empowerment strategies on body mass index, quality of life and self-management behavior were unclear. The improvements of both SBP and DBP were significant regardless of the duration and type of interventions. Abstract: Background: Cardiovascular disease has caused heavy health care burdens in many countries, and hypertension (HTN) is a well-known independent cardiovascular risk factor. Objective: To assess the efficacy of empowerment strategies that affect systolic blood pressure (SBP), diastolic blood pressure (DBP), body mass index (BMI), quality of life, and self-management behaviours for patients with hypertension. Methods: A literature search of the Cochrane Library, PubMed, MEDLINE, Embase, Web of Science, and several Chinese medical databases was performed. Study screening, quality assessment, data extraction, and meta-analysis were conducted according to Cochrane standards. Results: Eleven randomised controlled trials with 988 subjects were identified. Relative to control groups, the empowerment strategies showed significant decreases in SBP (the mean difference [MD] = 9.46, 95 % confidence interval [CI] = 6.36–12.55, p < 0.00001) and DBP (MD = 6.68, 95 % CI = 3.07–10.29, p = 0.0003). However, no significant difference was found in BMI ( p = 0.05). Subgroup analysis showed significant differences in the improvement of both SBP and DBP among the various groups, regardless of the duration and type of interventions. Discussion: Empowerment strategies can decrease both SBP and DBP in hypertension patients. However, its influence on patients' BMI, quality of life, and self-management behaviour remains unclear. Practical value: Empowerment strategies are useful for controlling the blood pressure of hypertension patients.